Diversity of bird species in Sandik City Park , West Lombok as ecotourism support - Zulhariadi, Muhammad; Amin, Saleh (Generasi Biologi Indonesia, 2022)
West Lombok is one of the areas on the island of Lombok which has a lot of tourist charm, especially natural tourism. Birdwatching is a bird watching activity that can increase environmental awareness and a source of economic income for tourism managers (ecotourism). The purpose of this study was to determine the diversity of bird species in Sandik City Park located in West Lombok. Bird observation using the Encounter Rates method. From the results of the study, 11 species of birds were found, consisting of honey-sucking, insect-eating, and grain-eating species. The value of bird species diversity was in the medium category (H'=2.28), with the highest number of birds dominated by the Passer montanus. The Scaly-crowned Honeyeater (Lichmera lombokia) is a bird typical of the island of Lombok that can be found easily along with other honey-sucking birds in the morning at Sandik City Park. The primadoma plant perch for chirping birds in the garden is the Coral Tree (Erythrina crista-galli). By knowing the level of diversity of bird species and the characteristics of their preferred habitat, it is necessary to serve as a guide for the government in managing city parks to be more friendly to animal life, especially birds. Preservation of birds that are maintained in city parks is a feature of habitat sustainability which indirectly brings economic benefits to park managers.